Let's simplify the expression \( 7\sqrt{3} - 4\sqrt{6} + \sqrt{48} - \sqrt{54} \).
-
Simplifying \( \sqrt{48} \): \[ \sqrt{48} = \sqrt{16 \times 3} = \sqrt{16} \cdot \sqrt{3} = 4\sqrt{3} \]
-
Simplifying \( \sqrt{54} \): \[ \sqrt{54} = \sqrt{9 \times 6} = \sqrt{9} \cdot \sqrt{6} = 3\sqrt{6} \]
-
Substituting back into the expression: \[ 7\sqrt{3} - 4\sqrt{6} + 4\sqrt{3} - 3\sqrt{6} \]
-
Combining like terms:
- For \( \sqrt{3} \): \[ 7\sqrt{3} + 4\sqrt{3} = 11\sqrt{3} \]
- For \( \sqrt{6} \): \[ -4\sqrt{6} - 3\sqrt{6} = -7\sqrt{6} \]
-
Final simplified expression: \[ 11\sqrt{3} - 7\sqrt{6} \]
Now, let's look at the answer choices:
a) \( 11\sqrt{6} - 7\sqrt{12} \)
b) \( 11\sqrt{3} - 7\sqrt{6} \)
c) \( -3\sqrt{9} \)
d) \( 4\sqrt{9} \)
The correct answer is b) \( 11\sqrt{3} - 7\sqrt{6} \).